Meningkatkan Hasil Belajar Siswa Pada Tema Aku Anak Soleh Melalui Model PBL (Problem Based Learning) Pada Siswa Kelas IV SDN 13 Malampah Utara - Wati, Idoy (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Education is an essential aspect of human life aimed at developing personal potential through the learning process. At SD Negeri 2 Lubuk Layang, the teaching of Islamic Education still uses conventional methods, leading to passive students and low learning outcomes. This study aims to improve students’ learning outcomes in the topic of "Mari Mengaji" and "Mengkaji QS. at-Tin" through the implementation of the cooperative learning method, specifically the Make a Match technique. It is hoped that this method will activate students and make learning more engaging and meaningful. Based on the observations, the application of this method has proven to increase student involvement and their learning outcomes. This study shows that the use of the Make a Match technique can enhance students’ learning outcomes and have a positive impact on their motivation to learn.